2021
DOI: 10.1002/tesq.3070
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality for Pragmatics Task Development

Abstract: This study intends to contribute to the methodological debate into L2 pragmatics research by examining the usability of immersive virtual reality (VR) for developing a pragmatics task. The study compared participants’ speech act performance between two closed role‐play tasks using different mediums: computer‐based and VR‐based. Sixty‐two native and nonnative speakers of English completed both tasks eliciting speech acts (requests, refusals, and opinions). The impact of task medium was assessed on oral fluency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…It is likely that this cognitive process might lead to the IP group’s slower and more cautious utterances. This finding aligns with the findings of previous L2 pragmatics studies (e.g., Taguchi, 2022). Taguchi (2022) found that L2 learners’ speech rate was significantly lower when producing PDR-high pragmatic features than PDR-low pragmatic features.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is likely that this cognitive process might lead to the IP group’s slower and more cautious utterances. This finding aligns with the findings of previous L2 pragmatics studies (e.g., Taguchi, 2022). Taguchi (2022) found that L2 learners’ speech rate was significantly lower when producing PDR-high pragmatic features than PDR-low pragmatic features.…”
Section: Discussionsupporting
confidence: 93%
“…A questionnaire with a five-point Likert-type scale entailing the target test items was conducted with 22 L1 speakers of American English and 10 proficient L2 speakers. The questionnaire adapted Taguchi’s (2022) survey and asked the 32 L1 and L2 speakers to rate how easy or challenging it was to perform the target pragmatic features (1 = very easy , 5 = very challenging ). The results showed a significant difference between the PDR-high scenarios ( M = 4.10, SD = .29) and the PDR-low scenarios ( M = 2.18, SD = .61), t = 16.336, p < .001, d = 2.888 (large), suggesting that the target speech acts in the PDR-high scenarios were perceived as more challenging to perform compared with the target pragmatic features in the PDR-low situations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are questions for further research, which could also work to determine what game-like elements are most effective in certain contexts and/or for certain tasks. Pedagogically, we see incredible promise for this line of work in the low-tech form described by Hernandez-Gonzalez and Gunning as well as high-tech variations afforded by the increasing use of immersive virtual reality and game-based language learning (e.g., Taguchi, 2021).…”
Section: Selected Talks From the Symposiummentioning
confidence: 99%